2021
DOI: 10.1371/journal.pone.0252681
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of COVID-19 influences on the wellness of Thai health professional students: An ambulatory assessment during the early “new normal” informing policy

Abstract: The COVID-19 global pandemic has had a socioeconomic effect, including many people suffering from stress and mental disorders. Health professional students are at risk of health issues as well when compared to their age-matched counterpart in the population. The present study aimed to find out the impact of COVID-19 awareness on the wellness of Thai health professional students. The awareness of COVID-19 and wellness among Thai health professional students, such as medical, physical therapy, nursing, pharmacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
7
10
0
Order By: Relevance
“…The current findings revealed that participants generally had positive attitudes regarding “new normal” guidelines, similar to previous reports ( 28 , 41 ). We found that 82.6% of participants agreed that “It's important to maintain a distance of at least 2 meters to prevent the spread of COVID-19,” which is similar to the findings of a previous study in Bangladesh ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current findings revealed that participants generally had positive attitudes regarding “new normal” guidelines, similar to previous reports ( 28 , 41 ). We found that 82.6% of participants agreed that “It's important to maintain a distance of at least 2 meters to prevent the spread of COVID-19,” which is similar to the findings of a previous study in Bangladesh ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
“…The findings revealed that many participants frequently engaged in practices regarding the “new normal” guidelines, which was similar to previous findings ( 28 , 36 , 41 ). In addition, 95.5% of participants always wore masks when they went to public places.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One study that was done among Thai health professional students found that COVID-19 awareness was negatively associated with anxiety symptoms. However, a positive association was found between COVID-19 awareness and mood, social well-being, and quality of life (Tiaprapong et al 2021 ). Another study that was done across 8079 Chinese junior and senior high school students showed significance between level of awareness and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%